How not to research public spheres: A new “dream of a physics of librarianship” - Buschman, John (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2021)
Research attention has been focused on the public sphere and librarianship recently, generating disagreement, even controversy. This reflects long-running debates in LIS and related fields. This is not a stale rehash: how we think about the public sphere and libraries is an indicator of libraries in democratic societies and how we position them. A compact account of affinity groupings around this research in LIS will precede an account of the controversy suggesting the question, are there still actually existing public spheres as Habermas deployed the term? The answer clarifies the controversy, and the paper will explore and draw conclusions from it.